Green Human Resource Management: A Literature Review - Cahya Purnama Asri (Profesional Muda Cendekia Publishing, 2021)
Over the past 10–15 years, the global business context has changed rapidly, and many organizations are now seen to be pursuing multiple purposes. Consequently, they are redefining success in more sustainable terms of Triple Bottom Line, Quadruple Bottom Line, and common good outcomes, not just financial criteria. Green human resource management (GHRM) is an arising issue for the tannery industry in the context of developing economies, as the tannery industry can be seen as one of the highest polluting industries on earth, it becomes imperative for the industry to implement GHRM practices for greening the workforce. For every country, macroeconomic sustainability is the main aim of improving the social welfare of the people, therefore, environmental performance needs to be improved without reducing the financial growth. The objective of this research is to determine the factors associated with non-performing loans. I presented a literature study using a systematic literature review of relevant publications and as a result of this process, 14 articles are included and then examined the bibliographical references to check the validity of the inquiry and to avoid any potential omissions. I identify several variables that are affected by GHRM. I find no outside variables, and strongly suggest research for outside variables.